Veno-venous extracorporeal membrane oxygenation for COVID-19-associated pediatric acute respiratory distress syndrome. (September 2020) - Lewis, Deirdre; Fisler, Grace; Schneider, James; Sweberg, Todd; Murphy, Kristina; Sathya, Chethan; Silver, Peter; Taylor, Matthew D
Background: The SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) coronavirus has emerged as a highly contagious respiratory pathogen causing severe acute lung injury. Extracorporeal membrane oxygenation is a standard tool for the management of life-threatening acute respiratory distress syndrome, but the use of this resource-intensive therapy has come into question due to strained medical systems and limited proven treatments for COVID-19. Case summary: A 16-year-old female with obesity presented with fever, myalgias, cough, and tachypnea and was diagnosed with COVID-19. She progressed to severe pediatric acute respiratory distress syndrome requiring intubation on hospital day 4 and cannulation to veno-venous extracorporeal membrane oxygenation on hospital day 6. The patient received remdesivir, steroids, and anakinra. The patient was successfully decannulated on hospital day 12 and was discharged home on hospital day 21. Conclusion: We report the use of veno-venous extracorporeal membrane oxygenation as a bridge to lung recovery in a pediatric patient with severe pediatric acute respiratory distress syndrome due to COVID-19.